A new species of Phyllurus leaf-tailed gecko (Lacertilia: Carphodactylidae) from The Pinnacles, north-east Australia - Hoskin, Conrad J.; Bertola, Lorenzo V.; Higgie, Megan (Zootaxa, 2019)
Recent surveys of rocky rainforest in the Townsville region have found additional populations of Phyllurus geckos. One of these populations was discovered at The Pinnacles, an isolated area of habitat in between the distributions of P. gulbaru and P. amnicola. Genetic and morphological data shows that this population is most similar to P. gulbaru Hoskin, Couper & Schneider, 2003 but divergent in a number of traits. Here we describe this population as a new species, P. pinnaclensis sp. nov., based on genetic divergence and differences in a number of morphometric and scalation traits from other populations of Phyllurus. Phyllurus pinnaclensis sp. nov. appears to be restricted to a few small areas of deeply layered rock with associated dry rainforest. This habitat is fire-sensitive and increased frequency and intensity of fires (due to late season burns and high fuel loads of invasive grasses) threatens to reduce and fragment these dry rainforest patches. Other threats include potential future invasion of the habitat by introduced Asian House Geckos (Hemidactylus frenatus Duméril & Bibron, 1836) and illegal collecting. Given the very small and fragmented distribution and potential reduction in habitat area due to fire, P. pinnaclensis sp. nov. warrants a Critically Endangered listing. Resolving the distributional change of dry rainforest in the Townsville region in recent decades, particularly in regards to fire, is key to resolving the status of this and other locally threatened taxa that depend on this habitat.